Arundhati Roy’s The God of Small Things (TGST): Diaspora - Shiva Zaheri Birgani; Maryam Jafari (SIASAT, 2020)
This paper attempts to analyze the mentioned novel based on postcolonial studies in Arundhati Roy's The God of Small Things. The concepts that can be mentioned in this novel are history, diaspora, hybridity, the role of women in Indian society, globalization, resistance and orientalism. These concepts are used from postcolonial theorists, Homi K. Bhabha . Colonization is a period of time. This is history itself. In developing the dominance of colonization, writers played a main role. Knowledge and power are the dominating themes that over-rule the deep nature of imperialism and literature. These themes indicate the superior literature, culture and tradition as the standard form of acceptance. Colonization is a period of time. This is history itself. In the result of the colonization, the migration and transition were not avoidable issues. Therefore, in this displacement, the new identity has been made. People’s customs, cultures and beliefs are mixed with colonizers’ unconsciously. India is a multicultural country. There are many various cultures in this country. And also during the colonization and the dominance of Britain over India, the changes were made in its customs and cultures. Arundhati Roy is an Indian writer and female activist.